UNCERTAINTY AND THE DYNAMICS OF AGGREGATE INVESTMENT IN MOROCCO - E. Ezzahid; A. El Alaoui; A. Bousselhami; M. Hamzaoui (European Scientific Journal, ESJ, 2014)
Investment is at the core of the process of economic growth. Most theoretical and empirical studies prove that it is a sine qua non factor of growth. The rates of aggregate investment in Morocco exhibited a declining or at best a stagnant trend since the end of the 1970s. External shocks, policy shifts, and domestic problems explain this situation. The uncertainty faced by economic agents may be a factor behind the poor performance of aggregate investment in Morocco. The results provide ambiguous conclusions. It is not evident if uncertainty measured by the conditional variance of two underlying variables affects investment or not. More research must be undertaken to improve the techniques of measuring the extent of uncertainty in the Moroccan economy and to identify its links with investment.